Improving Civics Learning Outcomes on the Material of Rules at Home with the PjBL Learning Model (Project Based Learning) - Suparni, Suparni (Universitas Sebelas Maret, 2022)
Ditulis The purpose of this study was to determine the improvement of learning outcomes of grade II students in the PPKn subject of Home Rules material after using the PjBL (Project Based Learning) learning model. This research uses PTK (Classroom Action Research) which is carried out in two cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, execution, observation and reflection. Based on the results of the study, when compared from cycle I to cycle II there was a significant increase in learning outcomes where in cycle I an average value of 69 was obtained increased in cycle II to 80. Then the number of students who completed in the first cycle was 13 people with a completion percentage of 57% increased in the second cycle to 21 students who completed with a percentage of learning completeness after using the project based learning learning model, amounting to 91%. And likewise with the required classical completeness of ≥80 has been achieved, thus this research was stopped until cycle II. From the results of the study, it was concluded that the use of a project-based learning model can improve the learning outcomes of grade II students of SDN 1 Buntalan, Klaten District, Mid-Academic Year 2022 / 2023.